Regulatory Pressure as a Moderator of the Effects of Environmental Performance, Environmental Costs, and Company Size on Financial Performance (E-Jurnal Akuntansi, 2026)
This study examines the effects of environmental performance, environmental expenditure, and firm size on the financial performance of mining companies listed on the Indonesia Stock Exchange between 2021 and 2023. It further considers the moderating role of regulatory pressure. Using purposive sampling, 32 companies were selected, yielding 96 firm-year observations. The proposed relationships were tested using moderated regression analysis. The findings indicate that environmental performance, environmental expenditure, and firm size are positively associated with financial performance. In addition, ISO 14001 certification, employed as a proxy for regulatory pressure, strengthens the positive associations between environmental performance and financial performance and between firm size and financial performance. However, regulatory pressure does not significantly moderate the relationship between environmental expenditure and financial performance. Overall, the findings suggest that compliance with recognised environmental standards may generate strategic and financial benefits, whereas environmental expenditure appears to remain primarily compliance-driven
Keywords: Financial Performance; Environmental Performance; Environmental Costs; Regulatory Pressure; Company Size